Studies on Packaging Materials for Storing Cauliflower Seeds in Modified Atmosphere - Kumar, P R; Sinha, S N; Sinha, J P (Journal of Agricultural Engineering, 2008)
Efficacy of modified atmospheres depends on the effectiveness of packaging materials in holding and containing the right mixtures of gasses for long periods. An experiment was carried out at Indian Agricultural Research Institute, Regional Station Karnal during 2005-06 to compare the ability of different packaging materials to retain the modified atmospheres. A gas mixture containing 60% CO2, 2% O2, and 38% N2 was filled in packets made of different packaging materials. The gas concentration was measured with the help of gas chromatograph periodically at an interval of 3 months up to 12 months period. It was found that aluminium foil lined low density polyethylene was found the best retainer of modified atmospheres for up to 12 months followed by ethylene vinyl alcohol co-polymer (EVOH or EVA).